Effects of radiant heat exposure on pacing pattern during a 15-km cycling time trial - Levels, K.; de Koning, J.; Broekhuijzen, I.; Zwaan, T.; Foster, C.; Daanen, H. (Journal of Sports Sciences, 2014)
The goal of this study was to investigate the effects of different durations of skin temperature manipulation on pacing patterns and performance during a 15-km cycling time trial. Nineteen well-trained men completed three 15-km cycling time trials in 18°C and 50% relative humidity with 4.5-km (short-heat), 9.0-km (long-heat) or without (control) radiant heat exposure applied by infrared heaters after 1.5 km in the time trial. During the time trials, power output, mean skin temperature, rectal temperature, heart rate and rating of perceived exertion were assessed. The radiant heat exposure resulted in higher mean skin temperature during the time trial for short-heat (35.0 ± 0.6°C) and long-heat (35.3 ± 0.5°C) than for control (32.5 ± 1.0°C; P < 0.001), whereas rectal temperature was similar (P = 0.55). The mean power output was less for short-heat (273 ± 8 W; P = 0.001) and long-heat (271 ± 9 W; P = 0.02) than for control (287 ± 7 W), but pacing patterns did not differ (P = 0.55). Heart rate was greatest in control (177 ± 9 beats/min; P < 0.001), whereas the rating of perceived exertion remained similar. We concluded that a radiant heat exposure and associated higher skin temperature reduced overall performance, but did not modify pacing pattern during a 15-km cycling time trial, regardless of the duration of the exposure.